Esensi Filosofis Dalam Kurikulum Konservatif Dan Progresivis: Suatu Analisis Komparatif - Elliani, Fetti; Walidin AK, Warul; Silahuddin, Silahuddin (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2025)
This study aims to analyze the philosophical essence of conservative and progressive approaches in the curriculum based on three main dimensions, namely epistemology, ontology, and axiology. This research uses a qualitative method with a library research approach. The data used are educational policy documents, educational theories, and relevant previous research results. The main data sources were obtained from academic databases, namely Google Scholar, official Ministry of Education documents, Merdeka Curriculum implementation reports, scientific journals, and academic books that discuss educational philosophy and curriculum implementation in Indonesia. The data collection technique is carried out through documentation studies by reviewing various references related to the research topic. The data analysis technique uses content analysis and comparative analysis to identify similarities and differences between conservative and progressive approaches in the curriculum. The results show that the conservative approach emphasizes stability in the education system by focusing on traditional values and fixed knowledge transmission, while the progressive approach prioritizes flexibility, learning experiences and innovation in the learning process. Both approaches have their own advantages and limitations, so their implementation requires a balance between the two to create an education system that is stable but still adaptive to changing times. The findings confirm that the ideal approach to education should combine the best elements of both approaches to produce learning that is more holistic and relevant to learners' needs. This research recommends further studies on the implementation of the balance between conservatism and progressivism in the education system, as well as regular evaluation of curriculum policies to ensure their effectiveness in improving the quality of education.